Bridging the Atlantic : Brazil and Sub-Saharan Africa, South–South Partnering for Growth - World Bank (World Bank, Washington, DC, 2017)
Bridging the Atlantic is a descriptive study of Brazil's involvement with counterparts in Sub-Saharan Africa through knowledge exchange, trade, and investments. The objective of the study is to understand these relations better with the intent to forge concrete and mutually beneficial partnerships between Brazil and Sub-Saharan Africa. Brazil and Sub-Saharan Africa are natural partners, with at one point a shared geography and later a shared history. Since the turn of the twentieth century, Africa has become one of the major fronts of Brazil's international agenda. Africa is rapidly changing and Brazil has expressed growing interest in supporting and taking part in African development. The study includes a narrative of the shared history between Brazil and Africa, as well as a description of Brazilian foreign direct investment and trade with Africa. It ends with recommendations made by the World Bank to strengthen the cooperation between Brazil and Sub-Saharan Africa.